KONTAMINASI MERKURI (Hg) DALAM ORGAN TUBUH IKAN PETEK (Leiognathus equulus) DI PERAIRAN ANCOL, TELUK JAKARTA - Etty Riani (Jurnal Teknologi Lingkungan, 2010)
Mercury (Hg) which is contained in aquatic ecosystem can enter and be accumulated to organism’s body, like on petek fish (Leiognathus equulus). The research aimed to see mercury concentration in aquatic ecosystem, to see mercury concentration in organ of petek fish by AAS (Atomic Absorption Spectrophotometer) and its histopathology response in organs of petek fish. The research was done at Ancol, Jakarta Bay on October-December 2004. There are 16 samples of water and fish from 3 stations.The analysis result of water quality is compared by standard quality of sea water for sea organism life (Kepmen LH No. 51, 2004), mercu ry concentration in fish organ is compared by maximum mercury concentration in fish body by classification of Palar (2004). Ancol water quality is still on normal condition. Mercury concentration in water and petek fish organs had low concentration. Gill and lever contaminated by mercuryis only in station 1 fish, but it is still on normal concentration. Histopathology of petek fish gill is not abnormal, while the lever is necrosis. Water and petek fish is not a good indicator to detect mercury in aquatic ecosystem.Keywords: mercury, petek fish, water, lever, gill, histopathology, accumulation,indicator